Developing the Nationalist and Religious Spirit Through the Synergy of the Four Pillars of Education - Rizaldis, Muhammad Jerit Aldo (Universitas Negeri Jakarta, 2024)
Background Education is the foundation in building a complete human civilization, through education a person can gain knowledge, skills and values that are the basis for personal and social life. Nationalism is a form of awareness of love for the land and water that aims to maintain the heritage of Indonesian customs and culture and foster an attitude of integrity in the nation and state. Purpose Cultivate the spirit of nationalism and religiosity through the synergy of the 4 pillars of education (formal education, Islamic education, religious figures, society). Design/method/approach Qualitative and quantitative research models. Results Through the synergy of the four pillars of education, nationalistic and religious nuances of education can be realized . Findings This show that each variable as a whole is declared significant or valid. And the results of the reliability test obtained a Cronbach's Alpha result of 0.836, which means that the instrument used in the reliability test meets the strong category. Contribution/value Education with nationalist and religious nuances can foster students' faith and science and technology.